The Effect of Traditional Games on Cooperation in Class VIII Junior High School 4 Purwadadi - Dani Febrianto; Citra Resita; Resty Gustiawati (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
The research was conducted to determine the effect of traditional games on student cooperation in physical education learning at junior high school. This research is an experimental research to find out whether the effect of traditional games on student cooperation in learning physical education. The number of samples was 32 students of class VIII B who were taken by technique cluster sampling by using a formula slovin. The data of this research is done by one group pretest-posttest design by using a student collaboration questionnaire using a scale likert distributed at the beginning and end of the meeting. The research results were obtained through a data normality test with the results stating that the data pretest 0.122 > 0.05 and posttest 0.142 > 0.05 from the results of the study showed that the data were normally distributed and through the calculation of the homogeneity test which showed a sig value of 0.734 > from 0.05 that the data pretest-posttest stating that the data is homogeneously distributed and the t-test calculation obtained the value of Sig.(2-tailed) 0.000 <0.05 indicates a significant difference between the results before and after being given treatment. It can be concluded that the results of the research conducted can be stated that there is an influence of traditional games on student cooperation in physical education learning at junior high school.